Financial Apps sebagai Media Edukasi Literasi Manajemen Keuangan - Dominika Dora Soge; Novi Wijayanti; Nur Annisa; Rudi Sanjaya (Jurnal Riset dan Inovasi Manajemen, 2024)
In this digital era, in carrying out their activities humans will not be able to be separated from the use of technology that can help humans in completing their tasks or help humans meet their needs more easily, including the people of Indonesia. The low awareness of Indonesian people in terms of financial literacy will certainly have an impact on their ability to manage finances. This study aims to analyze the role of Financial Apps as a medium of financial management literacy education. The use of Financial Apps is increasingly widespread and provides convenience for people in managing finances. Through a literature study, this research reveals that financial literacy has a high relevance to financial management skills. Individuals with good financial literacy tend to be wiser in planning, managing and controlling their finances. In this case, Financial Apps play an important role in improving financial literacy by providing features that make it easier for users to record transactions, create financial reports, and analyze financial performance.